2020
DOI: 10.1186/s13643-020-01491-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the nature of asthma in African epidemiological studies: a scoping review protocol

Abstract: Background Asthma is one of the most common chronic respiratory conditions in the world and is increasing in prevalence, particularly in Africa and other low-income countries. The disproportionately high numbers of premature deaths and severe or uncontrolled cases in many African countries are indicative of their inability to cope with a costly disease like asthma. Progress has, however, been made in understanding the complex and heterogeneous nature of the disease. The objective of this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…One of the most well-liked theories, the hygiene hypothesis, makes use of the fascinating interaction between the innate and acquired immune systems. According to this theory, the developed world's increased hygiene is a direct cause of the growth in asthma [12]. Even while this advancement has all but eliminated many infectious diseases like cholera, the lack of pathogen exposure in early children seems to cause allergies and asthma later in life.…”
Section: Asthmamentioning
confidence: 99%
“…One of the most well-liked theories, the hygiene hypothesis, makes use of the fascinating interaction between the innate and acquired immune systems. According to this theory, the developed world's increased hygiene is a direct cause of the growth in asthma [12]. Even while this advancement has all but eliminated many infectious diseases like cholera, the lack of pathogen exposure in early children seems to cause allergies and asthma later in life.…”
Section: Asthmamentioning
confidence: 99%
“…3 Asthma attacks are one of Africa's most serious public health issues and it claimed the lives of at least 400,000 people in 2016. 4 Also, an asthma attack is the 10th most common environmental burden by illness category [DALYs/1000 capita] per year in Ethiopia, with a prevalence rate of 9.1%. 5 Many research studies identified that asthma attack is influenced by numerous factors stemming from the environmental factors such as gene-environment interactions, environmental acquaintances, comorbidities, age, causal disease severity, health-care availability, psychological factors, disease response to management, and disease load, which includes asthma exacerbations and mortality, as well as long-term chronic morbidity.…”
Section: Introductionmentioning
confidence: 99%
“… 3 Asthma attacks are one of Africa’s most serious public health issues and it claimed the lives of at least 400,000 people in 2016. 4 Also, an asthma attack is the 10th most common environmental burden by illness category [DALYs/1000 capita] per year in Ethiopia, with a prevalence rate of 9.1%. 5 …”
Section: Introductionmentioning
confidence: 99%